NJI 2014
DOI: 10.48029/nji.2014.cv604
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Indian Turmeric Powder with Honey as Complementary Therapy on Oral Mucositis : A Nursing Perspective among Cancer Patients in Mysore

Abstract: Oral mucositis is a common, debilitating complication of cancer patients undergoing chemotherapy and radiotherapy, occurring in about 40 percent cases. Mucositis may limit the patient’s ability to tolerate chemotherapy or radiation therapy, and nutrition status is compromised. The aim of the study was to assess the effect of Indian turmeric powder with honey as a complementary therapy on treatment induced oral mucositis. In the study, quasi experimental nonequivalent control group pre test post-test design was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Patients receiving the treatment also experienced less weight loss and better treatment compliance. , A similar study showed that gargling with turmeric mouthwash delayed the occurrence of radiation-induced oral mucositis in HNC . A combination of turmeric and honey remarkably improved oral mucositis assessment scores in patients undergoing chemotherapy . Additionally, a microgranular formulation of curcumin (C3 complex) had better bioavailability and inhibited expression of fibroblast growth factor 2, granulocyte macrophage colony-stimulating unit, and IL-17 in head and neck cancer .…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients receiving the treatment also experienced less weight loss and better treatment compliance. , A similar study showed that gargling with turmeric mouthwash delayed the occurrence of radiation-induced oral mucositis in HNC . A combination of turmeric and honey remarkably improved oral mucositis assessment scores in patients undergoing chemotherapy . Additionally, a microgranular formulation of curcumin (C3 complex) had better bioavailability and inhibited expression of fibroblast growth factor 2, granulocyte macrophage colony-stimulating unit, and IL-17 in head and neck cancer .…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
“…280 A combination of turmeric and honey remarkably improved oral mucositis assessment scores in patients undergoing chemotherapy. 281 Additionally, a microgranular formulation of curcumin (C3 complex) had better bioavailability and inhibited expression of fibroblast growth factor 2, granulocyte macrophage colonystimulating unit, and IL-17 in head and neck cancer. 282 A randomized controlled trial showed that oral curcumin supplementation (300 mg, twice a day) for 6 months reduced burning sensation, increased mouth opening flexibility, tongue protrusion, and cheek flexibility in patients with oral submucous fibrosis (OSF).…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
“…The authors reported significant improvement of all clinical periodontal parameters in comparison with control group [75]. Moreover, curcumin gel has been shown to significantly reduce the severity and the size of lesion of mucositis in patients undergoing head and neck cancer radiotherapy [76,77]. Similarly, curcumin mouthwash expedited wound healing compared with 0.2% chlorhexidine mouthwash in radio-chemotherapy-induced oral mucositis patients [78].…”
Section: Curcuminmentioning
confidence: 99%